Patient preference and recall of results of EUS-guided FNA - Early, Dayna S. (2006)
BACKGROUND: There are no clear guidelines regarding the best way, in terms of timing and setting, to deliver results to patients who undergo EUS-guided FNA (EUS-FNA) of suspected pancreatic masses. OBJECTIVE: We aimed to study (1) whether patients undergoing EUS-FNA prefer to receive preliminary results immediately after the procedure or at a later date, after final results are known; and (2) to assess the accuracy of patients’ recollection of information given to them regarding their FNA diagnosis. DESIGN: We enrolled patients presenting to our endoscopy center for EUS-FNA of suspected pancreatic masses and obtained data through 4 pilot surveys. SETTINGS: University-based endoscopy center. PATIENTS: Sixty patients who were referred for EUS-FNA of suspected pancreatic masses. RESULTS: A total of 57 of 59 patients (96.6%) wanted preliminary results the same day as the procedure. Twenty-eight of 60 (42.7%) knew they were having a biopsy, and 42 of 60 (70%) knew cancer was suspected. Of those who received preliminary results, 31 of 41 (75%) remembered the diagnosis correctly the next day, and 32 of 38 (84%) remembered the diagnosis correctly 1 week later. LIMITATIONS: Single-center pilot study. CONCLUSIONS: The majority of our patients wished to receive preliminary results the same day as the procedure. Although most patients remembered results correctly, 25% of patients did not remember the correct diagnosis the next day. Further work is needed to improve patient’s understanding of the reasons for the EUS-FNA and recall of preliminary EUS-FNA results.